12.6 W single-frequency continuous-wave 671 nm laser with an external second harmonic generation cavity. (13th August 2020) - Liu, Xu-Chao; Wang, Zhi-Min; Zhang, Yi-Xuan; Zhou, Zi-Han; Zhang, Feng-Feng; Liu, Qian-Qian; Xu, Yi-Chen; Song, Yue; Yang, Rui-Nan; Zong, Nan; Bo, Yong; Peng, Qin-Jun; et al.
Abstract: We present a high-power single-frequency continuous-wave (CW) 671 nm laser by the second-harmonic generation (SHG) of a 1342 nm laser based on an external bow-tie enhancement cavity. Different from previous works, and using periodically poled nonlinear crystals for the SHG, we adopt the high damage-threshold nonlinear crystal lithium triborate (LBO) in the external SHG cavity to achieve a high-power CW SHG. In our experiment, with a type-II noncritically phase-matched LBO, an up to 12.6 W CW 671 nm laser is obtained with a 24 W incident 1342 nm laser, corresponding to an SHG conversion efficiency of 52.5 %. To our knowledge, this is a new record of power for the single-frequency CW 671 nm laser.